Argumentação e estratégias textual-discursivas em uma sentença absolutória: violência machista contra a mulher - Tomazi, Micheline Mattedi; Cabral, Ana Lúcia Tinoco (Language and Law / Linguagem e Direito, 2017)
This article presents an analysis of a court ruling which aims to: 1) check the textual-discursive signs which enable us to identify a discourse that socially validates the acquittal of the defendant in a case of violence against a woman; 2) identify the linguistic strategies used by the judge as arguments to procrastinate the judicial decision. The analyses are based on the Sociocognitive Approach to Context postulated by van Dijk (2012, 2014), along with studies carried out by Ducrot (1984) on Language Argumentation and by Kerbrat-Orecchioni (1997) about Language Subjectivitiy in enunciation. The analyses show that the judge, when judging certain cases of violence against women – mainly ones resulting in minor injuries – helps to promote a macho ideology that conceals, rejects or even denies the violence that was perpetrated by the defendant, in favor of a positive picture of the aggressor, thus endorsing his acquittal.